Pengaruh Ekstrak Buah Apel (Malus Sylvestris) Terhadap Perubahan Warna Gigi dalam Proses Bleaching (Pemutihan Gigi) Berdasarkan Perbedaan Waktu - Saputra, Deny; Amalia, Rosa (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2008)
A good bleaching process need to be seen from its time distance, the longer time process to done the better result will release. The aim of this research is to know the inï¬‚uence of apple extract in different time for bleaching process (tooth whitening), that used as an alternative materials for tooth whitening. Design of this research is laboratory experimental, by using 15 tooth specimen and Rome Beauty apple extract of 5 0%, 100% and aqudes as negative control. Three groups have given diï¬‚erent continue treatment, they are groups of soaked 24 hours, 48 hours and 72 hours with concentration of extract 50% and 100%. Aï¬er soaked, the changing colour value would be observed by using spectrophotometer:Research result show that value degree of change of colour before and after soaked with apple extract 50% and 100% with group of soaked 24 hours, 48 hours and 72 hours. Based on paired T-Test result showed that there was changing of tooth colour that turn into whiten Based on Friedman Analysis result show that P=0.324 (p 0,05), which means that there was not significant inï¬‚uence time in tooth whitening changing with apple extract in tooth whitening process with time 24 hours, 48 hours and 72 hours with extract concentration 50% and 100%. Several factor inï¬‚uence the result, such as too short time distanceso that the calculation of statistic did not show any signiï¬cant changing the sample is fewer so that there was not inï¬‚uence in calculation of statistic.